Immunological and metabolic effects of cis-9, trans-11-conjugated linoleic acid in subjects with birch pollen allergy - Turpeinen, Anu M.; Ylönen, Niina; von Willebrand, Eva; Basu, Samar; Aro, Antti (British journal of nutrition, 2008)
Animal studies suggest that conjugated linoleic acid (CLA) may modulate the immune response, while studies in healthy human subjects have shown little effect and results are controversial. However, the effects of CLA may be more prominent in situations of immune imbalance, such as allergy. We studied the effects of the natural CLA isomer, cis-9, trans-11-CLA, on allergy symptoms and immunological parameters in subjects with birch pollen allergy. In a randomised, placebo-controlled study, forty subjects (20–46 years) with diagnosed birch pollen allergy received 2 g CLA/d in capsules, which contained 65·3 % cis-9, trans-11-CLA and 8·5 % trans-10, cis-12-CLA (n 20), or placebo (high-oleic acid sunflower-seed oil) (n 20) for 12 weeks. The supplementation began 8 weeks before the birch pollen season and continued throughout the season. Allergy symptoms and use of medication were recorded daily. Lymphocyte subsets, cytokine production, immunoglobulins, C-reactive protein, lipid and glucose metabolism and lipid peroxidation were assessed before and after supplementation. The CLA group reported a better overall feeling of wellbeing (P < 0·05) and less sneezing (P < 0·05) during the pollen season. CLA supplementation decreased the in vitro production of TNF-α (P < 0·01), interferon-γ (P < 0·05) and IL-5 (P < 0·05). Total plasma IgE and birch-specific IgE concentrations did not differ between groups, whereas plasma IgA (P < 0·05), granulocyte macrophage colony-stimulating factor (P < 0·05) and eosinophil-derived neurotoxin (P < 0·05) concentrations were lower after CLA supplementation. Urinary excretion of 8-iso-PGF2α, a major F2-isoprostane (P < 0·01), and 15-keto-dihydro-PGF2α, a primary PGF2α metabolite (P < 0·05), increased in the CLA group. The results suggest that cis-9, trans-11-CLA has modest anti-inflammatory effects in allergic subjects.